2010
DOI: 10.1111/j.1752-7325.2010.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring conceptual health knowledge in the context of oral health literacy: preliminary results

Abstract: Objectives Health literacy encompasses several abilities including word recognition, reading comprehension, communication skills, and conceptual knowledge. To date, conceptual knowledge has not been included in oral health literacy research. This study assesses the validity and reliability of a new instrument and describes conceptual oral health knowledge among a sample of low-income adults. Methods One hundred Baltimore adults were administered the Rapid Estimate of Adult Literacy in Medicine (REALM), Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(214 citation statements)
references
References 9 publications
11
191
2
3
Order By: Relevance
“…Comprehensive measures of oral health knowledge scores were significantly associated with age, education level, and annual household income. 6 In this study, highly significant associations were found between patients' age, education, monthly income and oral health literacy level (P=0.000). In another analytic study, their mean age was 26.6 years (SDo=o6.9).…”
Section: Conflict Of Interestmentioning
confidence: 73%
See 1 more Smart Citation
“…Comprehensive measures of oral health knowledge scores were significantly associated with age, education level, and annual household income. 6 In this study, highly significant associations were found between patients' age, education, monthly income and oral health literacy level (P=0.000). In another analytic study, their mean age was 26.6 years (SDo=o6.9).…”
Section: Conflict Of Interestmentioning
confidence: 73%
“…To date, conceptual knowledge has not been included in oral health literacy research. 6 Researchers hypothesize that an individual's health literacy is represented by a constellation of skills and abilities, including word recognition, reading comprehension, communication proficiency, and conceptual knowledge. 7 Lack of education along with traditional beliefs and socio-cultural factors lead to development of false perceptions and myths.…”
Section: Figurementioning
confidence: 99%
“…Accumulating evidence suggests that health literacy also has a pivotal role in the context of oral health (Horowitz and Kleinman, 2008;Parker and Hernandez, 2012). Recent studies have detected links between lower literacy and poor outcomes in the domains of oral health status (Parker and Jamieson, 2010;Lee et al, 2012;Wehmeyer et al, 2013), knowledge (Macek et al, 2010), and quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Several published conceptual frameworks on OHL include a complex web of associations between OHL and self-efficacy/ dental knowledge (Macek et al 2010; U.S. Department of Health and Human Services 2010; Lee and Divaris 2014). The relationship between general health literacy and self-efficacy is also highlighted in the literature (Wolf et al 2007;Torres et al 2009;Osborn et al 2010).…”
Section: Introductionmentioning
confidence: 99%